IMPROVING INSTRUCTIONAL PRACTICES IN LITERACY: SUPPORTING THE GROWTH AND DEVELOPMENT OF INTERVENTION TEACHERS - Guzman, Monica Marie (East Carolina University)
The goal of the participatory action research study was to examine how intervention teachers contribute to the improvement of literacy instructional practices in elementary schools. A team of nine elementary intervention teachers volunteered to participate and engage in three cycles of inquiry throughout the 14-month study. Collaborating more frequently with a smaller group of intervention teachers as three co-practitioner researchers, we identified experiences and practices to support the growth and development of the team of intervention teachers in their work to increase literacy in schools. To develop relational trust and identify the supports they needed to be effective in their work, the team engaged in Community Learning Exchanges to share effective instructional practices and strategies as they collaboratively addressed literacy needs at their schools. The study describes how participants navigated fragmented centralized reform efforts and the impact made on literacy intervention instruction and outcomes. The findings of the study reveal the need for established systems of support for the team of intervention teachers. In addition, by clarifying their complex roles and providing relevant professional learning, the challenges the intervention teachers faced were minimized. These findings support and add to the research literature in the areas of supporting the development of the capacities and practices of teachers in specialized roles.
Keywords: Education, Educational Leadership